Exploring type 2 inflammation and disease complexity: perspectives of a clinical immunologist - Yuval Tal; Limor Rubin; Ariel Munitz; Irit Adini (Frontiers in Immunology, 2026)
Type 2 inflammatory diseases are often grouped together as a single immunological entity, driven by shared cytokines and overlapping pathways. This framework has led to the development of biologic therapies targeting upstream epithelial-derived “alarmins”, including thymic stromal lymphopoietin (TSLP), interleukin (IL)-33, and interleukin (IL)-25. These mediators promote downstream cytokine responses, most notably IL-4, IL-5, and IL-13, which orchestrate type 2 inflammation across multiple tissues. Despite these shared molecular features, type 2-associated diseases exhibit substantial clinical heterogeneity and variable responses to targeted therapies. A notable example is TSLP blockade, which has shown significant clinical efficacy in asthma but failed to demonstrate similar benefit in atopic dermatitis. From a clinical immunology perspective, we explore the complexity of type 2 inflammation. We discuss the dual pro- and anti-inflammatory roles of TSLP isoforms (long form and short form), the contribution of compensatory inflammatory pathways, and the impact of the tissue microenvironment on disease-specific immune responses. These factors may underlie divergent therapeutic outcomes despite targeting a shared upstream mediator. A better understanding of this complexity may help explain the limitations of a linear, cytokine-centered model of type 2 inflammation and support the development of more precise therapeutic strategies, including targeting shared downstream signaling components and combination approaches.